Regulation of the cell cycle (CC) of Vicia faba L by the alcoholic extract of Annona cherimola Mill "cherimoya" - Beltrán, Raúl A. (2016)
The likely antineoplastic effect of extract of Annona cherimola Mill "chirimoya", is controversial. Therefore, such as neoplasia involves an alteration of the cell cycle (CC) of the affected tissue; an approach to evaluate the antineoplastic effect of extract would be exposing it to a cell population with the altered CC. The aim of this study was to evaluate the effect of alcoholic extract from the pulp of the fruit of A. cherimola Mill on the CC of the biosensor Vicia faba L. "bean" exposed to the food coloring tartrazine 0.1%, 0.3% and 0.5%. An experimental design was random, with six treatments. The cell population studied was of V. faba L. (2n = 12), initially submitted to tartrazine to induce the alteration of CC and then exposed to the extract of the fruit of A. cherimola Mill to assess the likely regulation of the CC. The indicator of alteration and cellular regulation was the mitotic index (MI) of V. faba L. To determine the MI, cells were subjected to the protocol Tjio and Levan (1968), then it was observed an average of 1500 cells by treatment, in a light, field microscope light, 400 x and 1000 X. The data were submitted to Anova and Tukey tests (α = 0.05). It was found that the alcoholic extract of the pulp of the fruit of A. cherimola Mill if it regulates the cell cycle of V. faba L., altered by tartrazine, by generating an MI of 19.2 ± 2.0 finding significant difference. Therefore the summary would provide components that contribute in cell recovery mechanisms.